Situación laboral de la mujer en Castilla y León - Maya Frades, Antonio; Hidalgo González, Cristina (Geographicalia, 2016)
The long lasting importance of rural economy in the society of the Autonomous Region of Castile and Leon (Spain) resulted in the fact that women rarely worked outside farms. However, since the 1970's, women have joined the work force of this region, even though in smaller numbers than in other Spanish regions. Among other factors that have influenced this situation we can quote the small dynamism and capacity of this region's economy to diversify production and create jobs suitable for the relevant female population, who suffers higgher unemployment rates.
Keywords: Woman; labour market; Castile and Leon; equal opportunities